Bojonegoro Regency Transportation Agency Innovation in Free Student Transportation Services - Lestari, Jihan Regina; Andriamiandrisoa, Hoby Nasandratra (Universitas Bojonegoro, 2026)
Innovation is a process that involves the introduction of new elements into organizational services. One of the government's innovations is student transportation. Student transportation is a transportation service provided by the government, this service not only reduces the burden of parents' costs, but also ensures the safety of students on their way to school. This service also contributes to increasing student attendance and punctuality to school, which has a positive impact on the quality of education. This study aims to determine how the Bojonegoro Regency Transportation Agency innovates in providing free student transportation services in 2024. This study was conducted using qualitative methods. The collection technique was carried out through literature studies and field studies through: interviews, questionnaires and observations. Determination of samples/informants in this study was carried out using purposive sampling. Innovation success factors were measured using the theory of Cook, Matthews, and Irwin. The final results of this study concluded that the innovation of the Bojonegoro Regency Transportation Agency in providing free student transportation services in 2024 was not fully successful, the results of this study indicate that there are still several things that must be considered by the Bojonegoro Regency Transportation Agency in determining the success of free student transportation service innovations.